Animación sociocultural: revisión teórica y reformulaciones actuales - Víctor J. Ventosa Pérez (Centro Universitário Salesiano de São Paulo, 2016)
The purpose of this article is focused on testing what have been the constants and which variables practices Animation Sociocultural (ASC) over more than half a century of its existence, in order to discover that common denominator which has remained as a constant thread and anchor identity, distinct from the circumstantial envelope in which it has been presented throughout the different contexts and historical situations. This approach will allow us to meet the necessary reformulation and adaptation of the ASC to a new era, a new Society of characteristics significantly different from those of half a century ago where the paradigms of the twentieth century in which settled, need revision in light new situations and philosophical and scientific contributions of the new millennium, in order to deal with a new type of diseases characterized by increasing complexity that demand global responses to global problems Societies, fleeing therefore partial, Manichaean and outdated approaches. This review will reconsider the epistemological status of Sociocultural Animation as Teaching Participation defining and focusing its object in the teaching and learning of participation, as the author develops in his latest book: Teaching Participation (Ed Narcea, Madrid, 2016) forthcoming in Brazil (SESC, Sao Paulo).